2019
DOI: 10.1016/j.chest.2019.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Costs of Workplace Productivity Loss in Patients With Fibrotic Interstitial Lung Disease

Abstract: BACKGROUND: Fibrotic interstitial lung diseases (ILDs) are highly morbid chronic disorders that frequently occur in working age individuals. The goal of this study was to determine workplace productivity loss, its determinants, and its estimated costs in patients with fibrotic ILD. METHODS: Patients with idiopathic pulmonary fibrosis, chronic hypersensitivity pneumonitis, idiopathic nonspecific interstitial pneumonia, or unclassifiable ILD were identified from the six-center Canadian Registry for Pulmonary Fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Similar to the findings in patients with non-CTD FILD ( 6 ), productivity loss in patients with CTD-FILD assessed by the Work Productivity and Activity Impairment (WPAI) questionnaire was reported by 59% of employed patients. The analysis demonstrated a substantially more important role of percent productivity loss, hours lost, and cost resulting from presenteeism (51% or 5.5 ± 0.7 hours lost per week or an average annual cost of 7,876 CAD per patient) compared with that driven by absenteeism (24% or 3.9 ± 0.9 hours lost per week or an average annual cost of 5,717 CAD per patient).…”
supporting
confidence: 77%
See 1 more Smart Citation
“…Similar to the findings in patients with non-CTD FILD ( 6 ), productivity loss in patients with CTD-FILD assessed by the Work Productivity and Activity Impairment (WPAI) questionnaire was reported by 59% of employed patients. The analysis demonstrated a substantially more important role of percent productivity loss, hours lost, and cost resulting from presenteeism (51% or 5.5 ± 0.7 hours lost per week or an average annual cost of 7,876 CAD per patient) compared with that driven by absenteeism (24% or 3.9 ± 0.9 hours lost per week or an average annual cost of 5,717 CAD per patient).…”
supporting
confidence: 77%
“…However, the often much costlier counterpart of absenteeism and the less visible contributor to workplace productivity loss is presenteeism—being on the job, but because of illness, not fully functioning. Indeed, a recent study by Algamdi and colleagues using data from a six-center Canadian Registry for Pulmonary Fibrosis (CARE-PF) showed that among 650 patients with idiopathic fibrotic ILD (FILD), chronic hypersensitivity pneumonitis, and unclassifiable FILD, only 148 (23%) were employed ( 6 ). Productivity loss was reported by 55% of employed patients, with absenteeism affecting 14% and presenteeism affecting 52% of patients.…”
mentioning
confidence: 99%
“…Algamdi et al [ 23 ] similarly looked at the economic impact of fibrotic interstitial lung diseases (ILDs), including workplace productivity loss and the associated costs. The researchers used the Work Productivity and Activity Impairment questionnaire in patients in the six-center Canadian Registry for Pulmonary Fibrosis (CARE-PF) and compared them to Canadian population census data.…”
Section: Economic Consequences Of Occupational Lung Diseasementioning
confidence: 99%
“…An average productivity loss of 7.8 ± 0.9 h per week was found. Presenteeism accounted for the majority of this loss (5.5 ± 0.6 h per week), while absenteeism accounted for a smaller proportion (2.3 ± 0.6 h per week) [ 23 ]. This study demonstrates the significant economic impact of fibrotic interstitial lung diseases.…”
Section: Economic Consequences Of Occupational Lung Diseasementioning
confidence: 99%
“…The cost components used to determine indirect costs was variable. Two Canadian studies specifically focused on work productivity loss in fibrotic ILD (Table 1 ) [ 16 , 17 ]. Productivity loss associated with absenteeism and presenteeism refers to loss as a result of absence from work and working with limitations due to illness, respectively [ 18 ].…”
Section: Resultsmentioning
confidence: 99%